2009
DOI: 10.1007/s00209-009-0577-9
|View full text |Cite
|
Sign up to set email alerts
|

Upper bound for the Lempert function of smooth domains

Abstract: Abstract. An upper estimate for the Lempert function of any C 1+ε -smooth bounded domain in C n is found in terms of the boundary distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In the same paper the authors showed the opposite estimate for C 1+ε -smooth domains with z 1 , z 2 near ζ 0 ∈ ∂D. This estimate in the bounded case follows from the inequality for the Lempert function of bounded C 1+ε -smooth domains obtained by Nikolov, Pflug and Thomas [6]. It was also proved that the above estimate fails in the C 1 -smooth case.…”
Section: Introduction and Resultsmentioning
confidence: 67%
“…In the same paper the authors showed the opposite estimate for C 1+ε -smooth domains with z 1 , z 2 near ζ 0 ∈ ∂D. This estimate in the bounded case follows from the inequality for the Lempert function of bounded C 1+ε -smooth domains obtained by Nikolov, Pflug and Thomas [6]. It was also proved that the above estimate fails in the C 1 -smooth case.…”
Section: Introduction and Resultsmentioning
confidence: 67%
“…Remark. (a) The Dini-smoothness is essential as an example of a C 1 -smooth bounded simply connected planar domain shows (see [8,Example 2]). (b) One of the missing properties of b D in comparison with c D and l D is monotonicity under inclusion of (planar) domains.…”
Section: Resultsmentioning
confidence: 99%
“…(this proof uses only the existence of an appropriate supporting (real) hyperplane and the formula for the Poincaré distance of the upper halfplane). On the other hand, by [13,Theorem 1], for any C 1+ε -smooth bounded domain there exists a constant c > 0 such that…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…The smoothness is essential as an example of a C 1 -smooth bounded C-convex planar domain shows (see [13,Example 2]). Moreover, using [16,p.…”
mentioning
confidence: 99%